Diplomasi Indonesia dan Perlindungan Pekerja Migran di Arab Saudi, 1975–1986 - Ishak, Andaru Maulana (Forum for Social and Humanities Studies, 2025)
This article discusses the diplomatic relations between Indonesia and Saudi Arabia concerning the placement of Indonesian Migrant Workers (TKI) during the period from 1975 to 1986. The main objective of this paper is to analyze Indonesia's diplomatic policies and strategies in managing and protecting the presence of TKI in Saudi Arabia. During this period, Saudi Arabia became one of the primary destinations for Indonesian migrant workers, particularly in the domestic sector, which had a high demand for affordable and skilled labor. Indonesian diplomacy at the time focused on establishing bilateral cooperation through various agreements that regulated placement systems, labor rights, and legal protection efforts for TKI. Although these agreements were not as comprehensive as modern ones, they laid an essential foundation for managing labor relations between the two countries. However, several challenges persisted in practice, such as weak oversight of recruitment agencies, insufficient legal protection systems, and limited pre-departure education for prospective workers. These conditions made many TKI vulnerable to exploitation, abuse, and human rights violations. This study shows that Indonesian diplomacy played a significant role in shaping a more equitable cooperation framework with Saudi Arabia to enhance the protection of TKI. Although not yet perfect, these diplomatic efforts paved the way for improved management of migrant labor placement. Moving forward, strengthening the legal system, improving education, and enhancing the role of diplomatic missions abroad are key to ensuring the welfare and rights of Indonesian migrant workers in a sustainable manner.